Pengaruh Zeolit dan Zat Pengaktif Terhadap Kualitas Gas Propylene - Romadona, Wahyu; Melani, Ani; Atikah, Atikah (Penerbit Goodwood, 2024)
Purpose: This study aimed to synthesize and characterize ultrafiltration membranes based on polyethersulfone (PES) with the addition of titanium dioxide (TiO?) at concentrations of 0%, 1%, and 2% to evaluate its effect on membrane structure and water treatment performance. Research/methodology: Membranes were prepared via phase inversion using N, N-dimethylacetamide (DMAc) as the solvent and polyvinylpyrrolidone (PVP) as an additive. The characterization techniques used included FTIR (functional groups), SEM and AFM (morphology), contact angle measurements (hydrophilicity), porosity testing, and pure water flux analysis. Results: TiO ? addition significantly improved the membrane properties. Hydrophilicity increased as the contact angle decreased from 68.2° to 53.7. The porosity increased from 48.78% to 67.75%, and the 2% TiO? membrane exhibited the best surface structure and pore distribution. It also achieved the highest water flux at 5.77 L/m²·h, although still below the typical ultrafiltration standard (10–50 L/m²·h). Conclusions: Incorporating TiO? enhanced the hydrophilicity, porosity, and uniformity of PES membranes. The 2% TiO? membrane demonstrated optimal performance despite not achieving the standard ultrafiltration flux. Limitations: The limitations of this study include the non-uniform dispersion of TiO? particles and the testing conducted only under laboratory conditions, which may not accurately reflect real-world performance. Contribution: This study demonstrates the potential of TiO ? in improving PES membrane performance for water treatment and provides a practical reference for developing advanced ultrafiltration membranes for industrial applications.